Acute Myeloid Leukemia in Adolescents and Young Adults Treated in Pediatric and Adult Departments in the Nordic Countries. Issue 1 (18th August 2015) - Wennström, Lovisa; Edslev, Pernille Wendtland; Abrahamsson, Jonas; Nørgaard, Jan Maxwell; Fløisand, Yngvar; Forestier, Erik; Gustafsson, Göran; Heldrup, Jesper; Hovi, Liisa; Jahnukainen, Kirsi; Jonsson, Olafur Gisli; Lausen, Birgitte; et al.
Abstract : Background: Studies on adolescents and young adults with acute lymphoblastic leukemia suggest better results when using pediatric protocols for adult patients, while corresponding data for acute myeloid leukemia (AML) are limited. Procedure: We investigated disease characteristics and outcome for de novo AML patients 10–30 years old treated in pediatric or adult departments. We included 166 patients 10–18 years of age with AML treated according to the pediatric NOPHO‐protocols (1993–2009) compared with 253 patients aged 15–30 years treated in hematology departments (1996–2009) in the Nordic countries. Results: The incidence of AML was 4.9/million/year for the age group 10–14 years, 6.5 for 15–18 years, and 6.9 for 19–30 years. Acute promyelocytic leukemia (APL) was more frequent in adults and in females of all ages. Pediatric patients with APL had similar overall survival as pediatric patients without APL. Overall survival at 5 years was 60% (52–68%) for pediatric patients compared to 65% (58–70%) for adult patients. Cytogenetics and presenting white blood cell count were the only independent prognostic factors for overall survival. Age was not an independent prognostic factor. Conclusions: No difference was found in outcome for AML patients age 10–30 years treated according to pediatric as compared to adult protocols. Pediatr Blood Cancer 2015; 9999:1–10 © 2015 Wiley Periodicals, Inc.